Heterologous expression of lipase in Escherichia coli is limited by folding and disulfide bond formation - Xu, Y. L.; Yasin, A.; Tang, R.; Scharer, J. M.; Moo-Young, M.; Chou, C. P. (Applied Microbiology and Biotechnology, 2008)
Functional expression of lipase B from Pseudozyma antarctica (PalB) in the cytoplasm of Escherichia coli BL21(DE3) and its mutant derivative Origami B(DE3) was explored. Coexpression of DsbA was found to be effective in enhancing PalB expression. The improvement was particularly pronounced with Origami B(DE3) as a host, suggesting that both folding and disulfide bond formation may be major factors limiting PalB expression. Fusion tag technique was also explored by constructing several PalB fusions for the evaluation of their expression performance. While the solubility was enhanced for most PalB fusions, only the DsbA tag was effective in boosting PalB activity, possibly by both enhanced solubility and correct disulfide bond formation. Our results suggest that PalB activity is closely associated with correct disulfide bond formation, and increased solubilization by PalB fusions does not necessarily result in activity enhancement.